Exceptional crime in early modern Spain : taxonomic and intellectual perspectives - Río Parra, Elena del (Medieval and early modern Iberian world, 2019)
"Exceptional Crime in Early Modern Spain accounts for the representation of violent and complex murders, analysing the role of the criminal, its portrayal through rhetorical devices, and its cultural and aesthetic impact. Proteic traits allow for an understanding of how crime is constructed within the parameters of exception, borrowing from pre-existent forms while devising new patterns and categories such as criminography, the 'star killer, ' the staging of crimes as suicides, serial murders, and the faking of madness. These accounts aim at bewildering and shocking demanding readers through a carefully displayed cult to excessive behaviour. The arranged 'economy of death' displayed in murder accounts will set them apart from other exceptional instances, as proven by their long-standing presence in subsequent centuries"--